Candidates' perception on Malaysian University English Test (English Language): A case study at MARA University of Technology Dungun Campus / Mohd. Sharif Mohamad Noor - Mohamad Noor, Mohd. Sharif (2008)
When the Malaysian University English Test (MUET) was introduced, it has certain implications for the level of English Language (EL) proficiency among the undergraduates in the public universities. Taking from the cue, a research which uses questionnaires as the main source of data collection was administered on 86 undergraduates from various degree courses at MARA University of Technology (UiTM) Dungun Campus become the respondents. This research has three objectives, firstly , the researcher saw the need to provide feedbacks from the target group for consideration for improvements of EL program in universities, secondly, to determine the skills and course contents students regard as important and thirdly, to understand their attitudes towards MUET(EL) . The research reveals that the respondents do not have a positive attitude towards English thus affecting their MUET (EL) achievements to score a higher band thus the objectives of the research are achieved.